Dampak Masa Pandemi Covid-19 Terhadap Komunikasi Organisasi CRNTV UINSU - Ika Hardianti; Dewi Dokate Manalu; Taufik Hidayat; Hasan Sazali; Maulana Andinata (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
This study aims to show how organizational communication works during the covid-19 pandemic, and this study will show how the impact of the COVID-19 pandemic period on organizational communication. This type of research uses qualitative descriptive to obtain data and information about the Impact of the Covid-19 Pandemic Period on the Communications of the UINSU CRNTV Organization (Case Study of UINSU CRNTV Members). In this study, it was found that the Covid-19 pandemic had a serious impact on the intensity of communication within an organization. In the UINSU CRNTV organization itself, during the Covid-19 pandemic the communication was not good, due to the lack of activity from some members. This is due to several obstacles, including an unstable network, even for reasons that are out of control, because all activities are carried out online..